South African Old Testament studies and the future - Deist, Ferdinand (Old Testament essays, 1992)
South African Old Testament scholarship was born in the cradle of European and American scholarship and has grown to suffer from a lack of theological reflection as well as an inferiority complex that has made scholars lose sight of or underestimate the unique contribution the African perspective can make to the field of study. A plea is made for scholars to 'Africanise' Old Testament studies with a view to contributing to the international discussion. The major portion of my paper will be devoted to two rather serious problems in the history of South African biblical scholarship.